Media Promosi Gudnyus.id Berbasis Motion Graphic - Moch Calvin Ali; Arta Uly Siahaan; Muhammad Irwanda (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
Gudnyus.id is an online media and social news website concept. To support its popularity and bring out its existence, a promotional medium is needed. Based on the questionnaire that the author has distributed online via google form with the target of general public respondents in the urban center of Batam, information is obtained from the questionnaire, 60.6% of the public does not know while 39.4% knows, but only sees Gudnyus. Id posters or flyers on social media. Consequently, Gudnyus.id requires promotional support in the form of video, which is chosen because Gudnyus.id has no promotional support in the form of videos, particularly animated videos. In the production of promotional videos, the author uses the Villamil-Molina search method to support the design. There are five phases: development, pre-production, production, postproduction and delivery. The author uses the epic model method as an analysis to test the efficacy of Gudnyus.id's promotional media based on motion graphs. The information in the promotional video includes an introduction to Gudnyus.id as an online media, website heading, and the social media used by Gudnyus.id to transmit the information. from the output of the efficacy analysis using epic model, it’s known that the promotional video of Gudnyus.id based on the movement charts was found to be effective with an average value of 4.05 empathy, 4.26 persuasion, 4.0 impact, 4.22 Communication.